Adjusting the Ga grading during fast atmospheric processing of Cu(In, Ga)Se2 solar cell absorber layers using elemental selenium vapor. (8th February 2017) - Schmidt, Sebastian Simon; Wolf, Christian; Rodriguez‐Alvarez, Humberto; Bäcker, Jan‐Peter; Kaufmann, Christian Alexander; Merdes, Saoussen; Ziem, Florian; Hartig, Manuel; Cinque, Sonja; Dorbandt, Iris; Köble, Christine; Abou‐Ras, Daniel; et al.
Abstract: We study the sequential fabrication of Cu(In, Ga)Se2 (CIGSe) absorber layers by using an atmospheric pressure selenization with a process duration of only a few minutes and the utilization of elemental selenium vapor from independent Se sources. This technology could proof to be an industrially relevant technology for the fabrication of thin‐film solar cells. Controlling the amount of Se provided during the selenization of metal precursors is shown to be an effective measure to adjust the Ga in‐depth distribution. A reduced Se supply for CIGSe formation leads to a more homogeneous Ga distribution within the absorber. The underlying growth dynamics is investigated by interrupting the selenization at different times. At first, CIGSe formation occurs in accordance with previously suggested growth paths and Ga segregates at the Mo back contact. Between 520 and 580 °C, the growth dynamics differs distinctly, and In and Ga distribute far more uniformly within the absorber depth. We also studied the impact of the precursor architecture. The best performing precursor in terms of efficiency of the respective solar cells was a multilayer with 22 In/CuGa/In triple layers. Simple bilayers stacks lead to films of higher roughness and correlated shunting. By optimizing the precursor architecture and the Ga in‐depth distribution in the CIGSe layer, a conversion efficiency of up to 15.5% (active area) could be achieved. To our knowledge, this is the highest reported efficiency for sulfur free CIGSe‐based solar cells utilizing fast (few minutes) atmospheric processes and elemental Se vapor. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We study the Cu(In, Ga)Se2 absorber fabrication by fast atmospheric pressure selenization of metal precursor films utilizing elemental selenium vapor from independent sources. We find that a high Se supply during selenization leads to the generally observed Ga accumulation at the back contact, while a reduced Se supply leads to a more homogeneous Ga distribution within the absorber. By optimizing the precursor as well as the Ga in‐depth distribution in the CIGSe layer, a conversion efficiency of 15.5% was achieved.